Effect of Inflation on Economic Growth in Indonesia: The Moderating Role of Electronic Money Transaction - Meliza, M (KnE Social Sciences, 2024)
This research aims to examine the effect of inflation on economic growth in Indonesia from 2012 to 2021. Besides, this research also analyses the electronic money transaction role in the relationship between inflation and economic growth, especially after the Covid-19 phenomenon. The result of analysis shows that all variables are stationary at the first difference, while the Johansen cointegration test indicates long-run cointegration. On the other hand, inflation has a negative and significant effect on economic growth in the long run. In addition, electronic money transaction is successful in moderating the relationship between inflation and economic growth in the long run. Keywords: economic growth, electronic money, inflation